Geomorphological and sedimentological dynamic processes at the semi-closed Bay Platis Gialos (Sifnos Island) - Petropoulos, A.; Kapsimalis, V.; Evelpidou, N.; Anagnostou, Ch. (15th International Congress of the Geological Society of Greece, 2019)
Platis Gialos Bay located at the Southern part of Sifnos Isl. and his length is determined at 1.000 m, with SE direction. The coast of Platis Gialos Sifnos has been under erosion and permanent coastal retreat for several years, especially at the central and west part of the beach. The main causes of coastal erosion are anthropogenic.This paper focuses most intently on the geomorphological and sedimentological dynamic processes of the Bay which forming the current situation. For this reason a number of tasks took place in order to determine the level of disturbances of this dynamic equilibrium. This study included two phases of survey for two different periods (summer/winter). The first phase deals with the geomorphological and sedimentological coast characteristics, and includes: i) long-term geomorphological evolution of the coastal zone through the analysis of satellite images (Google Earth), in order to estimate the intensity of coastal erosion. ii) topographic sections at the surface of the coastal zone, through D-GPS (Spectra Precision SP80 GNSS Receiver), perpendicular to the coastline, iii) sediment sampling in the subaerial coastal area, iv) analytical recording and mapping of the summer and winter shorelines via the D-GPS, v) the situation of the potential feeders of the shore with materials, necessary for the formation of an alluvial beach, and vi) recording of land uses (Fig.1). The second phase, includes the geomorphological and sedimentological characteristics of the marine area, in particular: i) topographic sections of the bottom surface until the depth of 1.5 m, through D-GPS, perpendicular to the coastline ii)sediment sampling in the subaquatic marine area, iii) data of the numerical recomposition of the wind and wave conditions of the study area, iv) bathymetric eco-sonar data (Lowrance LCX-15MT), v) side-scan single beam eco-sounder (StarFish 450), to determine the seabed morphological features of the bay and, vi) substrate component mapping (Fig. 1). Laboratory analyzes were followed by the methods of dry granulometry, in order to categorize it, in different types on the basis of Folk & Ward (1957) method through GRATISTAT (v.8) software.